Causal Relationship Model of Environmental Education and Psychological Trait - Thiengkamol, Nongnapas (Richtmann Publishing, 2012)
Environmental education and psychological trait play important roles for global citizen to take responsible for theirbehaviors change through inspiration of public consciousness in daily life activity. This might be an successful environmentalbehavioral change to decrease the greenhouse gases by raising awareness, adjusting attitude and belief, increasing skill andparticipation with practice in daily living to accomplish sustainable development.The populations will be undergraduate studentsof academic year 2011 of Mahasarakham University. The Multi-stage random sampling was used to collect the sample for 450undergraduate students. The questionnaire was employed as instrument for data collecting. LISREL was used for modelverification. Results illustrated that considering on structural model confirmatory factors of EE and TRAIT were able to explainthe variation of endogenous factors of Inspiration of Public Consciousness (MIND) to caused Environmental Behaviors for GlobalWarming Alleviation (BEH) with 89.00 percents. Therefore, the equation 1, can be written as following:BEH = 0.32 MIND + 0.29 TRAIT + 0.75 EE ……………………..(1)(R2 = 0.89)Moreover, considering on structural model confirmatory factors of EE and TRAIT were able to explain the variation ofendogenous factors of Inspiration of Public Consciousness (MIND) with 97.0 percents. Therefore, the equation 2, can be writtenas following:MIND = 0.67 TRAIT + 0.58 EE …………………………………..(2)(R2 = 0.97)